Time-dependent behaviour of timber lightweight concrete composite floors - Jorge, L. (2010)
This article presents a study on the time-dependent behaviour of timber lightweight concrete composite floors. The option of using lightweight aggregates in concrete (LWAC), instead of normal weight aggregates, is the focus of this document. The load-slip behaviour of SFS-screwed joints in timber-LWAC structures is analysed both for the short term and the long term cases. The study takes advantage of an experimental programme carried out at the University of Coimbra where several timber-LWAC specimens were tested for 600 days. The load-slip behaviour of the connections is very important for the behaviour of the whole structure. The last aspect that is developed in this article concerns the time-dependent behaviour of LWAC composite floors. The calculated results obtained through the computer programme proHBV, developed at the University of Stuttgart, proved to be very close to those obtained from tests carried out at the University of Coimbra. As explained in this article, the direct application of the design rules for creep in concrete and timber, as presented in Eurocodes 2 and 5, results in great deviations from the actual behaviour of structures composed of two materials, timber and concrete. To overcome this difficulty, the authors also present a simplified procedure that can be taken as an extension of the Eurocode design philosophy. This simplified procedure does not need the use of computer programme proHBV, and is much more accurate than the current Eurocode proposals. The deviation of the simple design procedure from the test (even if a bit higher than that of proHBV) is in the order of usually accepted values for practical design, however, the advantage of this approach for the practice is decisive.